(untitled) (Medical Forum Monthly, 2021)
Objective: The objective was to compare the two ranges of energy flux density for treatment of tennis elbow using ESWT technique. Study Design: Quasi experimental study Place and Duration of Study: This study was conducted at the Kanaan physiotherapy & spine clinic from February 2020 till July 2020. Materials and Methods: A convenient sample of 50 was calculated by epitool software. Patients were divided into 2 groups of 25 patients in each group. Group A received shockwave therapy with an intensity of 0.3mJ/mm2 and Group B received intensity of 0.2mJ/mm2. The outcome variables are pain, maximal grip strength and Upper Extremity Functional Index. Results: Shockwave at 0.3mJ/mm2 was found to be more effective in improving pain and maximal Grip strength at the post-treatment level while both 0.3mJ/mm2 and 0.2mJ/mm2 were found equally effective on Upper Extremity Functional Index. Conclusion: This Study concluded that the patients who were treated with 0.3mJ/mm2 intensity of shockwave had better outcomes of Maximal Grip strength at 6th Month.